2020
DOI: 10.1007/s00167-020-06183-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparable mid-term revision rates of primary cemented and cementless total knee arthroplasties in 201,211 cases in the Dutch Arthroplasty Register (2007–2017)

Abstract: Purpose Long-term failure of total knee arthroplasty (TKA) is mostly due to loosening of the prosthesis. In this study, the short-and mid-term revision rates of cemented vs cementless TKAs were investigated. Comparable short-and mid-term survival rates of both ixation methods were expected. Methods Data on all cemented and cementless TKAs performed between 2007 and 2017 were retrieved from the Dutch Arthroplasty Register. The cumulative crude incidence of revision of cemented and cementless TKA was calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…More contemporary cementless knee components utilize highly porous surfaces to promote biologic fixation of the prosthesis [ [5] , [6] , [7] , [8] ]. Proponents of new-generation cementless knee designs cite numerous studies demonstrating no difference in clinical outcomes or long-term survivorship compared to cemented TKA designs [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Despite the growing number of studies demonstrating excellent outcomes and survivorship of cementless TKAs, there continues to be concerns regarding initial fixation of cementless knee components compared to cemented knee implants that provide immediate fixation.…”
Section: Introductionmentioning
confidence: 99%
“…More contemporary cementless knee components utilize highly porous surfaces to promote biologic fixation of the prosthesis [ [5] , [6] , [7] , [8] ]. Proponents of new-generation cementless knee designs cite numerous studies demonstrating no difference in clinical outcomes or long-term survivorship compared to cemented TKA designs [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Despite the growing number of studies demonstrating excellent outcomes and survivorship of cementless TKAs, there continues to be concerns regarding initial fixation of cementless knee components compared to cemented knee implants that provide immediate fixation.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with other recent reports, also reporting no loosening of the uncemented tibial or femoral component after cementless TKA [ 30 , 31 ]. Other reports revealed promising results regarding the revision rate due to aseptic loosening after cementless TKA with just slightly higher revision rates as well [ 20 , 25 ]. Some authors, however, reported higher revision rates due to aseptic loosening after cementless TKA [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The implant survival rate within this study of 97.8% with revision as endpoint is matching results from a systematic review of the literature [ 18 ]. Comparing survival rates of cementless and cemented TKA in general, there are reports of better all-cause survivorship of cementless fixation in TKA [ 23 ], while there are also reports stating no difference in mid-term survival between cementless and cemented fixation [ 25 , 37 ]. Regarding specific patient populations, cementless TKA showed a significantly lower revision rate in morbidly obese patients [ 2 ] and superior clinical outcomes with equal implant survival compared to cemented TKA in patients younger than 65 years [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would not have differed for the growth of this strain and development of a biofilm on the cement disks, with or without the gentamicin impregnation. Research on orthopedic bone cement should be aimed at gaining more insight into its role in PJIs as several studies reported higher revision rates in cemented implants compared to cementless implants ( Engesaeter et al, 2006 ; Quispel et al, 2021 ). Several other implant materials were not included due to lack of availability or difficulties in processing, such as cobalt-chromium alloys or ceramics.…”
Section: Discussionmentioning
confidence: 99%